Analisis Rencana Strategis Puskesmas sebagai Upaya Persiapan Penyusunan Rencana Strategis Badan Layanan Umum Daerah Puskesmas Pakuan Baru - Mekarisce, Arnild Augina; Ena Sari, Rumita (Syntax Literate, 2023)
Pakuan Baru Public Health Center has been a regional public service agency since 2017 so that it has the mandate of the Minister of Home Affairs Regulation to make a strategic plan based on regional public service agencies, but it has not been implied in the strategic plan in 2019-2023, besides that most health workers did not understand in depth how to make a strategic plan. The objectives of this study include analyzing the strategic plan of the Pakuan Baru community health center for 2019-2023 as an effort to prepare the strategic plan for the regional public service agency of the Pakuan Baru public health center for 2024-2028. This research method descriptive research with a qualitative approach. The subject of this research is the Pakuan Baru public health center. Data collection was taken from secondary data by reviewing documentation in August-November 2021. Data validity checking techniques by increasing diligence, using reference materials and triangulation techniques. The results of data analysis show that the strategic plan of the Pakuan Baru public health center is partly in accordance with the standards, but has not included a complete overview and organization, has not included revenue realization and expenditure realization, vision, mission, and policy direction, and the inclusion of repeated performance. It is expected that the public health center can carry out guidance and technical activities on public health center officers in the preparation of the strategic plan of the public health center of the regional public service agency.